THE EXISTENCE OF RENCONG MAKING AS A CULTURAL PRODUCT IN ACEH: A STUDY IN BAET RAYA DISTRICT ACEH BESAR REGENCY - Rika Andalya Bukhari; Bustami Abubakar; Asmanidar (Indonesian Journal of Islamic History and Culture, 2021)
This article is entitled "The Existence of Rencong Making as a Cultural Product in Aceh (A Study in Baet Raya, Sukamakmur District, Aceh Besar Regency)". Rencong is a typical traditional weapon that has become an icon of Aceh region, as it is called Tanoh Rencong (The Land of Rencong). In Aceh Besar, rencong is traditionally produced by the community. One of the rencong production areas is in Baet Raya, Sukamakmur District. The problems to be studied are how the existence of rencong making in Baet Raya, what are the obstacles faced by craftsmen in Baet Raya and how the community and Aceh Besar district government respond to the rencong making in Baet Raya. The method used in this research is descriptive analysis. Data was collected through observation, interviews and documentation. The selection of informants was completed by purposive sampling. From the results of the research, it is known that the existence of rencong making in Baet Raya continues to decline each year, as it could be seen from the decreasing number of teumpeun and rencong craftsmen. This is due to the many constraints in the production process such as lack of capital, high raw material prices, lack of public interest in rencong and it is difficult to take it out by plane if it is not decorated in a frame while the craftsmen could not afford with enough capital. The people of Baet Raya are grateful for the activity of rencong making because, in addition to increasing income, it preserves cultural products. On the other hand, there are also those who regret it as many youth decide to work in teumpeun instead of continuing their education to a higher level. The effort made by the community in preserving rencong making in Baet Raya is by teaching the young generation the skills of making rencong from the early age, while the form of conservation from the government is to exhibit the rencong at every important event such as the Aceh Cultural Week (PKA). However, the craftsmen admit that they have never received assistance from the government any more, especially since Covid-19 and it affects all rencong-making activities in Baet Raya. Therefore, government support is needed for the continuity of the existence of rencong making in Baet Raya.